Chromogranin A pathway: from pathogenic molecule to renal disease. Issue 3 (March 2020) - Mir, Saiful A.; Biswas, Nilima; Cheung, Wai; Wan, Ji; Webster, Nicholas; Macedo, Etienne; O'Connor, Daniel T.; Vaingankar, Sucheta M.
Abstract : Background: Chromogranin A (CHGA) is an index granin protein critical for biogenesis and exocytotic release of catecholamine storage granules. It is elevated in plasma of patients with sympathetic over-activity and kidney dysfunction. Several CHGA polymorphisms are associated with hypertensive kidney disease. Previously, we unraveled the molecular mechanism by which CHGA expression is regulated in African Americans carrying a genetic variation associated with hypertensive chronic kidney disease (CKD). Method: Experimental CKD mouse model were created by 5/6th nephrectomy (Npx) using wild-type and Chga−/− knockout mouse strains to delineate the role of CHGA in CKD. Result: Wild-type-Npx mice expressing Chga developed exacerbated azotemia and fibrosis as compared with their knockout-Npx counterparts. Gene expression profiling revealed downregulation of mitochondrial respiratory complexes genes consistent with maladaptive mitochondria in wild-type-Npx mice, contrasted to knockout-Npx. In healthy individuals, an inverse relationship between circulating CHGA levels and glomerular function was observed. In vitro, mesangial cells treated with CHGA-triggered nitric oxide release by a signaling mechanism involving scavenger receptor SR-A. The CHGA-treated and untreated mesangial cells displayed differential expression of cytokine, chemokine, complement, acute phase inflammatory and apoptotic pathway genes. Thus, build-up of plasma CHGA because of kidney injury served as an insult to the mesangial cells resulting in expression of genes promoting inflammation, fibrosis, and progression of CKD. Conclusion: These findings improve understanding of the role of elevated CHGA in the progression of CKD and reveal novel pathways that could be exploited for therapeutic strategies in hypertensive kidney disease. Abstract : Supplemental Digital Content is available in the text